Emerging networking technologies for industry 4.0 - Santhiya M.; Jeyalakshmi J.; Venu H. (IGI Global, 2024)
The conceptual, technological, and enabling frameworks of the original Industry 4.0 concept have all undergone significant changes. The next generation of Industry 4.0, also known as Industry 5.0, is emerging as a result of the evolution of Industry 4.0 and will require a combination of fresh new technologies. These breakthroughs come from a range of industries, such as artificial intelligence (AI), 5G technology and 6G mobile networks, ML with quantum computing, etc. Artificial intelligence (AI), 5G and 6G, and machine learning with quantum computing are expected to influence the original Industry 4.0. As mentioned, a new era of Industry 4.0 is currently emerging. The primary emerging enabling technologies for Industry 4.0 are surveyed in this chapter. Included in the topics mentioned are artificial intelligence (AI), internet of things, blockchain, 5G wireless technologies, 3D printing, biometrics, virtual and augmented reality, digital twin in 6G technology with case scenarios. 2023, IGI Global. All rights reserved.